Possible unconventional order parameter in single crystals of SrPt3P superconductor. (26th October 2022) - Cho, Kyuil; Teknowijoyo, S; Ghimire, S; Krenkel, E H; Tanatar, M A; Zhigadlo, N D; Kong, S; Kovnir, K; Prozorov, R
Abstract: Anisotropic properties of single crystals of SrPt3 P were studied using London penetration depth and electrical resistivity measurements. The upper critical field, H c 2 ( T ), was determined from four-probe electrical resistivity measurements for three orthogonal directions of a magnetic field with respect to the crystal. The London penetration depth, λ ( T ), was determined from the magnetic susceptibility of the Meissner–London state measured using a tunnel-diode resonator technique. Whereas H c 2 ( T ) and the normal-state ρ ( T ) are practically identical for all three magnetic field orientations, the London penetration depth shows significant unidirectional anisotropy. The low-temperature λ ( T ) is exponentially attenuated when a small excitation radiofrequency magnetic field, H rf, is applied along the c ′ ′ -direction, in which case screening currents flow in the a ′ ′ b ′ ′ -plane, while for the other two orientations, H r f ∥ a ′ ′ and H r f ∥ b ′ ′, the London penetration depth shows a much stronger, λ ( T ) ∼ T 2, variation. Such unusual and contrasting behavior of the two anisotropies, γ H T = H c 2, a b / H c 2, c = ξ a b / ξ c and γ λ T = λ c / λ a b, imposes significant constraints on the possible order parameter. Although our measurements are insufficient to derive conclusively the superconducting gap anisotropy, the order parameter with two point nodes and a modulation in the perpendicular direction is qualitatively consistent with the experimental observations.